Electromagnetic Analysis of Fringed Microstrip Lines on Porosified LTCC - Talai, Armin; Steinhäußer, Frank; Gmeiner, Björn; Bittner, Achim; Rüde, Ulrich; Schmid, Ulrich; Weigel, Robert; Kölpin, Alexander (Electromagnetics in Advanced Applications (ICEAA), 2013 International Conference on, 2013)
Recent investigations demonstrated that porosification of LTCC enables a local modification of material properties, in particular of the effective permittivity. These studies revealed that the electric field strength is highest at the lower conductor track edges on the porosified substrate. The local field strength peaks cause substantial influence on the effectiveness of permittivity reduction due near-surface material abrasions. In this paper, the influences of these randomly fringed boundaries on electromagnetic properties are investigated for different degrees of fraying. The gained results are compared to measured screen print edges by scanning electron microscope image analysis of co-fired and post-fired gold conductors, and will contribute for reliable circuit design on porous LTCC in the future. © 2013 IEEE.
UnivIS-Import:2015-04-16:Pub.2013.tech.IMMD.lsinfs.electr_6
Keywords: cofired; Conductor edge; field simulation; fringed microstrip; inhomogeneous substrate; LTCC; porosification; reduction of permittivity; structural modeling